Navigating By Attire: The Use Of Dress By Female Administrative Employees - Rafaeli, Anat; Dutton, Jane E.; Harquail, Celia V.; Mackie-Lewis, Stephanie Anne (Academy of Management Journal, 1997)
We conducted an inductive study of the everyday decisions about dress at work of female administrative employees in a university business school. Our findings reveal that dress is an attribute embedded in a variety of cognitive schemata that govern individuals' comprehension of and behavior at work. In acquiring and executing these schemata, employees make efforts that enhance their emotional preparedness for jobs and improve interpersonal relations. The study offers implications for theory and research on organizational symbolism, role taking, and the current practical trend toward relaxed dress.